The Influence of Corporate Social Responsibility, Corporate Characteristic, Family Ownership, Profitabilitas and Corporate Governance on Tax Avoidance - Anastasia Panjaitan; Azhar Maksum; Erwin Abubakar (Jurnal Mantik, 2021)
The study aims to determine the effect of corporate social responsibility, corporate characteristic, family ownership, profitabilitas and corporate governance at mining companies listed on BEI. The population of this study is mining companies listed on BEI 2009-2019. Study’s sample were selected by purposive sampling as many as 18 companies. Number of observation used of this study as many as 190 observations. This study to analyze data with help of Partial Least Square (PLS) methode. The result of this study showed that did not effect between corporate social responsibility, corporate characteristic and corporate governance to tax avoidance. But family ownership take negative effect to tax avoidance and profitabilitas take positive effect to tax avoidance.